Gene flow from North Africa contributes to differential human genetic diversity in southern Europe - Botigué, Laura R.; Henn, Brenna M.; Gravel, Simon; Maples, Brian K.; Gignoux, Christopher R.; Corona, Erik; Atzmon, Gil; Burns, Edward; Ostrer, Harry; Flores, Carlos; Bertranpetit, Jaume; Comas, David; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
Human genetic diversity in southern Europe is higher than in other regions of the continent. This difference has been attributed to postglacial expansions, the demic diffusion of agriculture from the Near East, and gene flow from Africa. Using SNP data from 2,099 individuals in 43 populations, we show that estimates of recent shared ancestry between Europe and Africa are substantially increased when gene flow from North Africans, rather than Sub-Saharan Africans, is considered. The gradient of North African ancestry accounts for previous observations of low levels of sharing with Sub-Saharan Africa and is independent of recent gene flow from the Near East. The source of genetic diversity in southern Europe has important biomedical implications; we find that most disease risk alleles from genome-wide association studies follow expected patterns of divergence between Europe and North Africa, with the principal exception of multiple sclerosis.